2021
DOI: 10.1212/cpj.0000000000001072
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences With Ambulatory Telehealth in Neurology

Abstract: Objective:To assess patient experiences with rapid implementation of ambulatory telehealth during the COVID-19 pandemic.Methods:A mixed methods study was performed to characterize the patients’ experience with neurology telehealth visits during the first eight weeks of the COVID-19 response. Consecutive patients who completed a telehealth visit were contacted by telephone. Assenting patients completed a survey quantifying satisfaction with the visit followed by a semi-structured telephone interview. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…13 A recent study assessed patient experience with telehealth during the COVID-19 pandemic in the ambulatory neurology clinic. 14 753 patients were included. Fifty-three percent had a video visit and 47% had a phone visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A recent study assessed patient experience with telehealth during the COVID-19 pandemic in the ambulatory neurology clinic. 14 753 patients were included. Fifty-three percent had a video visit and 47% had a phone visit.…”
Section: Discussionmentioning
confidence: 99%
“…Another study looked at the acceptability of telehealth visits for ALS patients and found that telehealth was generally viewed favorably by ALS patients, caregivers, and multidisciplinary team members 13 . A recent study assessed patient experience with telehealth during the COVID‐19 pandemic in the ambulatory neurology clinic 14 . 753 patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that patient-centeredness can be achieved virtually and is facilitated by strong pre-existing patient-provider relationships. 43 , 44 …”
Section: Section 1: When To Use or Not Use Telehealth In Neuro-oncologymentioning
confidence: 99%
“…In-person care also remains important for in-person evaluations such as nerve conduction testing. 74 Some of these barriers are potentially able to be addressed with trained telepresenters in some contexts but such approaches remain an area for future study, particularly in a prospective, controlled trial format to gauge the value of video examination for the broad range of neurologic conditions and population settings seen for care. 67…”
Section: Telehealth Modalitiesmentioning
confidence: 99%